2021
DOI: 10.1007/s00204-021-03134-9
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor (AHR) functions in infectious and sterile inflammation and NAD+-dependent metabolic adaptation

Abstract: Aryl hydrocarbon receptor (AHR) research has shifted from exploring dioxin toxicity to elucidation of various physiologic AHR functions. Exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is known to exert cellular stress-mediated sterile inflammatory responses in exposed human tissues but may be lethal in sensitive species. Inflammation can be thought of as the extreme end of a spectrum ranging from homeostasis to stress responses (sterile inflammation) and to defense against infection (infectious inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…TIPARP encodes a poly(ADP-ribose) polymerase regulating innate immunity and repressing type I interferon signaling [ 40 ]. It also modulates stem cell pluripotency, autophagy and gene expression, with induction by growth factors, viral infection, nuclear receptors, hypoxia and aryl hydrocarbon receptor (AHR) [ 41 ]. Prior studies establish TIPARP as a negative regulator of AHR and IFN-I signaling [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…TIPARP encodes a poly(ADP-ribose) polymerase regulating innate immunity and repressing type I interferon signaling [ 40 ]. It also modulates stem cell pluripotency, autophagy and gene expression, with induction by growth factors, viral infection, nuclear receptors, hypoxia and aryl hydrocarbon receptor (AHR) [ 41 ]. Prior studies establish TIPARP as a negative regulator of AHR and IFN-I signaling [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…TIPARP (a.k.a PARP7), TCDD-inducible poly [ADP-ribose] polymerase, is an ADP-ribosyltransferase that mediates the mono-ADP-ribosylation of target proteins to control gene expression. For example, it functions as a negative regulator of AHR, a ligand-activated transcription factor, to regulate biological processes such as angiogenesis, hematopoiesis, cell motility, and drug and lipid metabolism 31 , 32 . Although AHR disrupts the contact inhibition 33 , the function and mechanisms of TIPARP in the nucleus and cytoplasm are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that AhR is involved in the regulation of cellular metabolism in many types of cells by acting as a TF to control the expression of metabolism-related genes, by interacting with intracellular signaling pathways related to metabolism, or by disturbing mitochondrial function 56, 57 . AhR is expressed by various immune cells, and its signaling exerts integrative effects on the cellular environment and metabolism of the immune responses 58 .…”
Section: Discussionmentioning
confidence: 99%